Hyundai Ioniq Ev Car Acquisition Analysis to Support Vehicle Forensics Activities - Zulhair Jidan Dj. Tamu; Yudi Prayudi (Jurnal Indonesia Sosial Teknologi, 2025)
Electric cars are motorized vehicles that use an electric motor as the main driver, which is run by a rechargeable battery. Electric cars have several advantages compared to conventional motorized vehicles that use internal combustion engines, such as lower emissions, cheaper operating costs and better performance. This research aims to identify vehicle forensics acquisition techniques in electric cars using the OBD port, by studying vehicle data usage activities. The acquisition focuses on the Hyundai Ioniq EV electric car, using the OBD port method in data retrieval_, and focusing on logical acquisition. This evidence may include location history, and connected devices, including sudden braking events, gear shifts, wheel speeds, and vehicle acceleration. The results of this research show that the OBD port can be a source of information in vehicle forensics, data collection. There were 20 digital pieces of evidence found, such as ECU data, telematics data, sudden braking system, wheel speed and vehicle acceleration